INTRODUCING LITERATURE THROUGH ART WORK TO YOUNG LEARNERS - Fitra Elia; Betty Sailun (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
There are various ways in introducing and teaching literature to young learners. One of them is by telling stories. Some teachers tend to avoid this activity because of lack materials. Most teachers only use story books provided by schools. The research aimed to build students' creativity by making their own story books through art work. The sample rvas the llfth semester students ol Riau lslamic University who have taken English for young learner subject. Total sample was 25 students by using random sampling technique. This is a descriptive research'design which focused on teaching media created by students, and interview as the research instruments. The students were asked to create peek-over book. envelope book, pop-up book, paper bag book, shirt book, step book, fold-oul book, video book, journals. flip book, accordion book. and big book. The result was satisfying. Most of the students were able to input famous stories such as A Little Red Riding Hood, Malin Kttndang and Pray of the Frog, rhymes, and poems into colorful and artful books they created. They could also improve adapting literary rvorks rvhich lvere presented visually throughout video into a written form such as A Hungry Caterpillar and Pete lhe Catand His Four Grooty Buttons.The most favorite books created were pop-up books. Based on the inteiview. the students said that it was more challenging and interesting. It has been more eff'ective to encourage and motivate them to write and be confident rvith talent they have. They rvere also enthusiastic to read more literary works being adapted into their art r.vork. It can be concluded that introducing literature through art work is one of teaching media altematives rvhich can motivate young learners be more creative and more enjoyable in leaming English.